The Possible Bidirectional Relationship between Disease Severity in Androgenetic Alopecia and Seborrheic Dermatitis: A Cross-Sectional Study in a Tertiary Care Hospital - Dilek Menteşoğlu; Gökçe Işıl Kurmuş; Selda Pelin Kartal (Indian Dermatology Online Journal)
Background: Seborrheic dermatitis (SD) is the most common concurrent disease in patients with androgenetic alopecia (AGA). There are inadequate data to determine whether there is a relationship between AGA severity and SD severity. Aim and Objectives: This study aimed to investigate the presence and the severity of SD in patients with AGA, who were divided into groups based on the severity of AGA. Patients and Methods: We evaluated 311 patients aged ≥18 years who were diagnosed with AGA at the dermatology outpatient clinic between April and September 2023. Patients were divided into three groups according to AGA severity. We used the Clinical Severity Score Criteria to determine the severity of SD on the scalp. We subsequently compared the severity scores among the groups based on the severity of AGA. Results: The mean age was 41.5 ± 15.2 (range 18–85) years. Of these patients, 74 (23.8%) were female and 237 (76.2%) were male. SD was observed in 131 patients (42.1%). Among those with SD, 19.9% were female and 80.1% were male. As AGA severity increased, the prevalence of SD also increased (P = 0.28). Furthermore, there was a statistically significant difference in the SD scores as the severity of AGA increased (P < 0.001). Limitations: Small patient group and cross-sectional design. Conclusion: SD may affect the pathophysiology and severity of AGA.